POP PESTICIDES AND RECLAMATION METHODS (REVIEW) - А.А.Mamirova,; А.А.Nurzhanova,; V.V.Pidlisnyuk, (Academic Journal of Physical and Chemical Sciences, 2019)
A thorough analysis of the foci of pollution with POPs pesticides and the development of methods for the remediation of contaminated areas is one of the key areas of the Kazakhstan Republic strategic development plan. The huge production of POPs pesticides, their over-purchasing by agro-industrial companies, as well as changes in agricultural infrastructure related to the liquidation of collective farms, state farms and land privatization led to their accumulation in warehouses in many CIS countries, including the Republic. When they getinto the environment with rain, wind, as a result of floods, landslides and fires, they pose an environmental hazard to human health and the environment, both locally and globally. In this regard, the article presents a literature review on the problems of POPs pesticides and methods for their reclamation. Modern methods of obsolete pesticides disposal (isolation, burial, immobilization, soil washing, electro-reclamation, heat treatment, etc.) and methods of pesticide-contaminated lands reclamation (bioremediation, phytoremediation, and vermiremediation) are considered. Particular emphasis was placed on phytoremediation technologies for POP pesticides in soil and methods for increasing their effectiveness, since this technology is an economically viable and environmentally friendly technology. The conditions for optimizing the environment using chemicals (low molecular weight compounds, carbon materials (biochar) and nanomaterials) and plant-microbial associations to stimulate the development of the plant organism increase the phytoavailability of POPs pesticides and increase their mobility in soil and water systems are considered in detail.